A giant on the ground: another large-bodied Atractus (Serpentes: Dipsadinae) from Ecuadorian Andes, with comments on the dietary specializations of the goo-eaters snakes - Passos, Paulo (2018)
Body-size is significantly correlated with the number of vertebrae (pleomerism) in multiple vertebrate lineages, indicating that somitogenesis process is an important factor dictating evolutionary change associated to phyletic allometry and, consequently, species fitness and diversification. However, the role of the evolution of extreme body sizes (dwarfism and gigantism) remains elusive in snakes, mainly with respect to postnatal ontogeny in dietary preferences associated with evolution of gigantism in many lineages. We described herein a new species in the highly diversified and species-rich genus Atractus on the basis of four specimens from the southeastern slopes of the Ecuadorian Andes. The new species is morphologically similar and apparently closely related to two other allopatric giant congeners (A. gigas and A. touzeti), from which it can be distinguished by their distinct dorsal and ventral coloration, the number of supralabial and infralabial scales, the number of maxillary teeth, and relative width of the head. In addition, we discuss on the ontogenetic trajectories hypotheses and dietary specializations related to evolution of gigantism in the goo-eaters genus Atractus.